FY2018 Comoros Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2019)
The Country Opinion Survey in Comoros assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Comoros perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral/bilateral agencies, media, academia, the private sector, and civil society in Comoros on 1) their views regarding the general environment in Comoros; 2) their overall attitudes toward the WBG in Comoros; 3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Comoros; and 4) their perceptions of the WBG’s future role in Comoros.